Ordered Honeycomb‐Pattern Membrane†. Issue 12 (29th October 2020) - Yuan, Hua; Li, Guangzhen; Dai, Enhao; Lu, Guolin; Huang, Xiaoyu; Hao, Longyun; Tan, Yeqiang
Abstract : Ordered porous membranes have wide and important application prospects in the fields of filtration, separation, catalysis, biomedicine, etc ., and have attracted growing interest in the field of material science. Among diverse membrane preparation approaches, breath pattern method has been widely concerned due to its simplicity in the preparation, ease in tuning the structure/property and functionality of formed membranes, and broad utility for various polymers. With the development of material design, the application spectrum of breath figure membrane has been greatly expanded. However, since the pore morphology of porous membrane is influenced by many factors, the controlling mechanism of normalization has not been clear yet. In this paper, the research progress of film‐forming materials in recent years is reviewed, and the correlation between pore formation and pore morphology is discussed in details. This information will provide a systematic and in‐depth perspective for research in this filed and an important guideline for the preparation of the ordered porous films with divergent applications. Abstract : Ordered porous films based on breath pattern method has been widely concerned due to its simplicity in the preparation, ease in tuning the structure/property and functionality of formed membranes. In this paper, recent advance in the film‐forming materials are reviewed, and the correlation between pore formation and pore morphology is discussed in details. This information will provide a systematical view on this filed and an important guideline in the design and preparation of the ordered porous films for divergent applications.